Hubungan antara Self Control dan Fear of Missing Out (FoMO) pada Pengguna TikTok Generasi Z - Farsya Meyrasikhah; Ninawati Ninawati (YASIN, 2026)
Intensive TikTok use among Generation Z often gives rise to fear of missing out (FoMO), namely anxiety experienced when feeling left behind in terms of information or social activities, whereas self-control is regarded as an important factor that can reduce this tendency. This study aimed to examine the relationship between self-control and FoMO among Generation Z TikTok users. A quantitative correlational method was employed with 425 participants aged 18–25 years in the Jabodetabek area. Data were collected through online questionnaires using self-control scales and FoMOS, while data analysis used Spearman’s rho because the data were not normally distributed. The results showed a significant negative relationship between self-control and FoMO (r = –0.674; p < 0.001), indicating that the higher an individual’s self-control, the lower the level of FoMO experienced. These findings highlight the importance of self-regulation in reducing digital anxiety among Generation Z and provide a basis for developing digital literacy education programs and psychological interventions to promote healthier social media use.